IMPLEMENTASI BANTUAN SOSIAL BAGI PENYANDANG DISABILITAS DI KOTA PEKANBARU - Vuspita, Keke; Rusli SD, Zaili (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Disability is a people that get its human right and prosperity from the government. Social assistance is an effort for government to welfare all of disability, but the implementation of social assistance for disability, still have so many problem and need to be fix because the process is very lame and complicated. The purpose for this research is to know (1) the implementation of social assistance, (2) factors that affect the implementation of social assistance. Theory that been used in this research is Tachjan Theory: (1) A program to be held, (2) group target or community, (3) Implementor. This research are using descriptive qualitative method. The informan in this research is (1) a chief of social rehabilitation, (1) chief of social rehabilitation for disability, and (1) people that get social assistance. This research are using interview, observation , library studies and documentation using purposive sampling method for the source of information and data analyzing. The result of this research shows that the implementation of social assistance for disability in pekanbaru city still not satisfy, because lack of source of fund for disability in Pekanbaru city ,so the implementation of social assistance for disability didn’t goes as it’s have.Key Word: Implementation, Social Assistance, Disability